INDUSTRIAL WORKER CHARACTER DEVELOPMENT IN THE TEACHING AND LEARNING PROCESS OF VOCATIONAL SCHOOL STUDENTS - Fitri, Raisa (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2021)
The goal of this study is to examine how the Vocational High School of Machine Engineering Department teaches and learns about industry-based work character. An explanatory sequential mixed approach and the Countenance Stake assessment method are used in this case study. Input, process, and outcome make up the three parts of the Countenance Stake assessment method. According to result of average antecedent, transaction data, as well as response of students, the teaching and learning process in vocational schools was excellent at developing work character. Meanwhile, student professional character can also be shaped by external as well as internal factors such as their religious convictions, their commitment to truthfulness, their sense of responsibility, their ability to think creatively and innovatively, as well as their work ethic, passion, and respect for their coworkers.